Same-day versus delayed simulation imaging after placement of a perirectal hydrogel spacer for prostate radiotherapy - Fredman, Elisha; Weinstock-Sabbah, Miriam; Icht, Oded; Moore, Assaf; Shochet, Tzippora; Limon, Dror; Bragilovski, Dimitri (Frontiers in Oncology, 2023)
Introduction Placement of a perirectal hydrogel spacer has been demonstrated to reduce the risk of rectal toxicity from prostate radiation. Practices vary regarding the timing of CT simulation after hydrogel placement, and the ideal schedule remains unknown. Methods Thirty patients with localized prostate adenocarcinoma underwent transrectal ultrasound-guided placement of an iodinated SpaceOAR™ hydrogel prior to radiotherapy. Per evolving practice, 15 completed same-day simulation and 15 returned for simulation 1–2 weeks later. Hydrogel volume, perirectal distance, air-void volume, and rectal dosimetry per NRG GU005 were compared between CT simulation, 1st fraction Cone-Beam-CT (CBCT), and final CBCT. Results CT simulation occurred 8.8 ± 2.4 days after placement in the delayed group, with no significant difference in the interval between simulation and 1st fraction between groups (p = 0.165). Greater observed de-creases in hydrogel volume (0.57 cc vs. 0.04 cc, p = 0.0002), and perirectal distance at both mid-gland (1.32 mm vs. 0.17 mm) and tallest point (2.40 mm vs. 0.04 mm) were seen on 1st-fraction CBCT in the same-day group (p = 0.0039; p = 0.0002). Per dosimetry recalculated on 1st fraction CBCT, five (D3 cc and D50%) versus one (D50%) rectal dose parameters were exceeded in the same-day and delayed groups, respectively, and 10 versus one parameters had a relative increase of ≥ 20%. Conclusion Due to the evolving anatomic changes in the days following hydrogel placement, same-day simulation scanning may introduce unintended variability in rectal dosimetry at the time of prostate radiotherapy.